2003
DOI: 10.1182/blood-2002-07-2321
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a novel regulatory element in the erythroid-specific promoter of the human PKLR gene causes severe pyruvate kinase deficiency

Abstract: We established the molecular basis for pyruvate kinase (PK) deficiency in a white male patient with severe nonspherocytic hemolytic anemia. The paternal allele exhibited the common PKLR cDNA sequence (c.) 1529G>A mutation, known to be associated with PK deficiency. On the maternal allele, 3 in cis mutations were identified in the erythroid-specific promoter region of the gene: one deletion of thymine ؊248 and 2 single nucleotide substitutions, nucleotide (nt) ؊324T>A and nt ؊83G>C. Analysis of the patient's RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
1
38
0
2
Order By: Relevance
“…The erythroid-specific promoter and individual exons of PKLR, including flanking intronic regions, were amplified by PCR as previously described [van Wijk et al, 2003]. DNA sequence analysis was performed using the BigDye Terminator Cycle Sequencing Kit (Applied Biosystems, Foster City, CA) on an ABI 310 Genetic Analyzer (Applied Biosystems).…”
Section: Biochemical and Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The erythroid-specific promoter and individual exons of PKLR, including flanking intronic regions, were amplified by PCR as previously described [van Wijk et al, 2003]. DNA sequence analysis was performed using the BigDye Terminator Cycle Sequencing Kit (Applied Biosystems, Foster City, CA) on an ABI 310 Genetic Analyzer (Applied Biosystems).…”
Section: Biochemical and Molecular Analysismentioning
confidence: 99%
“…Haplotype analysis using the erythroid-specific promoter polymorphism -248delT [van Wijk et al, 2003], and polymorphisms in intron 5 (c.507151C4T), intron 11 (variable number of ATT repeats), and exon 12 (c.1705A4C, c.1738C4T, and c.1992T4C) showed an identical haplotype in all families: T-T-16-C-T-C. This suggests a single origin for c.331G4A in the Dutch population; we designated this variant PK Utrecht.…”
Section: The Novel Pgly111arg Pk Variant Is Prevalent In the Dutch Pmentioning
confidence: 99%
“…In contrast, the -83G3 C strongly reduces in vitro promoter activity. We concluded that the -83G3 C mutation in the erythroid-specific promoter of PKLR strongly downregulates promoter activity in vitro (35 Fig. 3).…”
Section: Dna-tf-binding Assaysmentioning
confidence: 99%
“…However, the incidence of reported promoter mutations in genes seems to depend on the extensiveness by which genes have been studied in the past and the severity of disease caused by the mutation [3]. Examples of diseases caused by promoter mutations are b-thalassemia [4], Bernard-Soulier syndrome [5], pyruvate kinase deficiency [6], familial hyper cholesterol emia [101] and hemo philia [7] (for a review, see [8]). In general, polymorphic sequence variations are considered to be rather harmless, especially if located in noncoding sections of a gene.…”
Section: Gene Promoter Mutationsmentioning
confidence: 99%